An Approach to provide Secure Storage using Self Destructing Erasure Codes - Anusha, B; Phani Praveen, S (International Journal of Computer Sciences and Engineering, 2025)
Several encryption schemes provide data confidentiality but at the same time functionality of the storage system is limited. A threshold proxy re-encryption scheme which is integrated with decentralized erasure code was proposed to formulate a secure storage system. This scheme provides robust and secure storage and retrieval and also lets the user forward the data to other users. The main technical contribution is that encoding operations over encrypted messages as well as forwarding operations over encoded and encrypted message are supported by this scheme.